Rancang Bangun Sistem Pengendalian Level Pada Tangki Penyimpanan Menggunakan Degree Of Freedom Analysis Dengan Tunning PID Berdasarkan Metode Cohen-Coon - Firmansyah Adi Nugroho; Prima Dewi Permatasari; Hendrik Elvian Gayuh Prasetya (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
The storage tank is one of the most important operating units used in the generation process. This operating unit functions as water storage which will later be used as raw material for making steam. To maintain the mass balance system and the energy balance system in the storage tank, a proper control system is needed. One of the variables controlled in this operating unit is implementing a level control system. In a process control system, key knowledge is needed, namely determining the process variable (PV), manipulated variable (MV), and disturbance variable (DV). If it is wrong in determining the three types of variables, then the output from the control system that we provide is not by the value we want (setpoint). Analysis of degrees of freedom (DOF) is used to determine the number of manipulated variables in the storage tank operation unit. To determine the number of variable numbers and the number of equation numbers can be used by looking at the mathematical equation model of the storage unit operation. Meanwhile, to determine the number of variables used in the above equation is to choose the type of variable that affects the process if the variable is changed. PID tunning needs to be done to determine the best proportional, derivative, and integral constant values, which later the output we want is the same as the setpoint value. Cohen Coon is a PID tunning method that can tolerate a constant amplitude oscillation state. Cohen-Coon is trying to improve the oscillation method by using the quarter amplitude decay method. The closed-loop response system, in this method, is made so that the response is in the form of a quarter amplitude decay. Quarter amplitude decay is defined as a transient response whose amplitude in the first period has a ratio of one quarter (1/4).